Kesenjangan antara Teori Etika Bisnis Islam dan Praktik Bisnis dalam Menghadapi Tantangan Bisnis Modern - Febriani, Fenti; Umairo, Tsania; Ma’arif, M. Ishom; Misidawati, Dwi Novaria (Ekonosfera: Jurnal Ekonomi, Akuntansi, Manajemen, Bisnis dan Teknik Global, 2025)
The rapid development of sharia business in the modern era is faced with the challenge of the gap between Islamic business ethics theory and contemporary business practices. This study aims to analyze this gap and examine the development of consistent standards and regulations to overcome this challenge. The research method used is qualitative with a literature review approach, which analyzes various literature related to Islamic business ethics, modern business practices, and sharia standardization. The results of the study indicate that the gap between theory and practice arises due to the dominance of the capitalist paradigm, global competitive pressures, and a lack of in-depth understanding of sharia principles. In addition, the fragmentation of inconsistent standards and regulations hinders the harmonization of sharia business practices globally. To overcome this, the study offers a holistic solution that includes the development of standards and regulations based on maqasid sharia, innovation in product and service design, and increasing education and awareness of Islamic business ethics. Thus, this study provides theoretical and practical contributions in creating a fairer, more transparent, and more sustainable business system in accordance with sharia principles.